Association of obesity with metastatic bone disease in prostate cancer: a case-control study - Claudia P. Pedraza-García; Irma Villarreal-Garza; José H. Treviño-Ortiz; Juan M. Ibarra-Hernández; Gustavo R. Govea-Torres; Patricia R. Ancer-Rodríguez; Alder E. Perales-Mendoza; Eduardo Espinoza-Valdes; Eloise E. Raymonde-Ferlay (Medicina Universitaria)
Background: This study aimed to determine the relationship between obesity and the risk of bone metastases in prostate cancer patients by analyzing clinical and anthropometric variables. Methods: A case-control study was conducted at the Nuclear Medicine Department of the University Hospital José Eleuterio González from May to October 2024. A total of 85 adult prostate cancer patients were included: 28 cases (with bone metastases) and 57 controls. Body mass index, body fat percentage, and other clinical parameters were evaluated. Results: Obesity, as determined by BMI at the time of bone scintigraphy, showed an inverse association with bone metastases (odds ratio 0.89; 95% CI: 0.123–0.76; p < 0.05), suggesting a potential protective effect. No significant association was observed between initial BMI or body fat percentage and metastases. Body fat percentage classified more patients as obese (71.43%) than BMI (33.33%) (p < 0.0001). Conclusions: Obesity based on BMI at the time of bone scintigraphy may have a protective role against bone metastases in prostate cancer. Findings emphasize the need to evaluate body composition in clinical management.